The Interaction Between Critical Thinking, Education and Belief in Conspiracy Theories among Young People (Aged 25–30) - Butvilauskaitė, Gintarė; Mikuličiūtė, Vita (Psichologija, 2025)
The goal of educational institutions (especially universities) is to foster critical thinking. However, with the rising popularity of social media and the rapid spread of unchecked information there, more and more people, especially young ones, are inclined to believe in conspiracy theories. This raises the question of whether university students are truly being taught critical thinking skills that would help combat misinformation. Therefore, this study attempts to analyze the interaction between education, critical thinking, and belief in conspiracy theories among young people (aged 25–30). The study involved 73 participants (M = 26.9; SD = 1.7). 36 have a university education (bachelor’s or master’s degree), 37 a nonuniversity education (secondary, secondary with professional qualification, or nonuniversity bachelor’s degree). Participants were provided with instruments to determine their level of belief in conspiracy theories and their critical thinking. The results show that critical thinking fully mediates the relationship between education and belief in conspiracy theories. Additionally, individuals with a university education have a higher level of critical thinking and are less likely to believe in conspiracy theories compared to those without a university education. Finally, a significant negative correlation was found between the critical thinking of young people and their belief in conspiracy theories.
Keywords: conspiracy theories; critical thinking; education